Morphology of the female reproductive system and seasonality in reproduction of the freshwater crab Arcithelphusa cochleariformis (Brachyura: Gecarcinucidae) - Sneha Dineshan; Arath Raghavan Sudha Devi (Nauplius)
Abstract This study details the female reproductive system morphology and seasonality in reproduction of the freshwater crab Arcithelphusa cochleariformis, widely distributed in the wetlands of Wayanad, India. Histo-morphological analyses reveal that the H-shaped female reproductive system displays the general eubrachyuran pattern. The seminal receptacle exhibits a novel combination of both heterotreme and thoracotreme patterns with ventrally attached oviduct and the presence of a mono-layered columnar secretory epithelium lining the dorsal and ventral regions. The simple type vagina, covered by a cuticle, follows the heterotreme pattern. The seminal receptacle and vagina undergo changes parallel to the annual mating and ovarian cycle. The seminal receptacle appears small, collapsed, enclosing very few secretions before mating in the proliferation phase and swollen, containing enormous spermatophores and seminal plasma after mating in the previtellogenic phase. The seminal receptacle has a withered appearance in the primary and secondary stages of vitellogenic phase and with decreased amounts of seminal plasma and several freely dispersed spermatozoa concentrated at the ventral region during the tertiary vitellogenic stage.